2013
DOI: 10.1111/jnu.12025
|View full text |Cite
|
Sign up to set email alerts
|

Older Patients’ Experiences of Heart Failure—An Integrative Literature Review

Abstract: Older patients have special care needs caused by their HF and other chronic conditions, coupled with those of great age. When symptoms of HF exacerbate, older patients are predominantly admitted to geriatric care rather than cardiac care units, implying restricted access to specialized treatment. Little is still known about the basis for self-care abilities from both healthcare provider and patient perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 53 publications
6
71
0
6
Order By: Relevance
“…In contrast, a systematic review conducted in 2010 concluded that the effects of contextual factors such as age, marital status, education, among others, need to be further studied (14) . More recently, an integrative literature review, in order to verify reported symptoms, experience with the disease and self-care in elderly patients with heart failure, suggests that the poor quality of life and frequent contact with severe symptoms make them more dependent elderly caregivers, indicating inadequate self-care (15) . As the ideal instrument for self-care assessment in hospitalized patients, the correlation between the scores of both scales used was low to moderate.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a systematic review conducted in 2010 concluded that the effects of contextual factors such as age, marital status, education, among others, need to be further studied (14) . More recently, an integrative literature review, in order to verify reported symptoms, experience with the disease and self-care in elderly patients with heart failure, suggests that the poor quality of life and frequent contact with severe symptoms make them more dependent elderly caregivers, indicating inadequate self-care (15) . As the ideal instrument for self-care assessment in hospitalized patients, the correlation between the scores of both scales used was low to moderate.…”
Section: Discussionmentioning
confidence: 99%
“…For community-dwelling older people with chronic diseases life is filled with challenges as they try to manage everyday life and cope with symptoms of different origins. Multi-morbidity is a condition that may cause loss of autonomy, disability, social isolation (Falk et al 2013) and frailty (Le Reste et al 2013) if the diseases are not well managed. Even so, research has shown that older people tend to report fewer symptoms compared to younger people (Goldberg et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previously published reviews offer a more general account of self-care in HF or the experience of living with HF [38][39][40][41][42][43], rather than care seeking decisions specifically, or do not go beyond summarizing what is already reported in the literature [44].…”
Section: Figmentioning
confidence: 99%